COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BETWEEN THE SOUTH WEST SULAWESI REGIONAL DEVELOPMENT BANK (BPD SULSELBAR) AND NORTH EAST KALIMANTAN REGIONAL DEVELOPMENT BANK (BPD KALTIMTARA) 2015-2020 PERIOD - Pasryb, A. Syahida Ulhaq; Ruma, Zainal; Ali, Ahmad; Musa, Chalid Imran; Anwar, Anwar (SULTANIST: Jurnal Manajemen dan Keuangan, 2022)
This study aims to find out how the financial performance comparisons between the South West Sulawesi Regional Development Bank (BPD Sulselbar) and the North East Kalimantan Regional Development Bank (BPD Kaltimtara) for the 2015-2020 period. The parameters used to compare the financial performance of the two banks are using the ratio of Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), Good Corporate Governance (Self-Assessment) and Capital Adequacy Ratio (CAR). In this study, data analysis techniques were used, namely descriptive comparative analysis using the RGEC (Risk Profile, Earnings, Good Corporate Governance (GCG) and Capital) method which was supported by statistical testing, namely the independent sample t-test. Based on the results of descriptive comparative analysis using the RGEC method, it was found that the financial performance of BPD Sulselbar which was included in good criteria based on industry standards, namely the ratio of NPL, ROA, BOPO, GCG, and CAR ratio while for BPD Kaltimtara the ratio of NPL, LDR, ROA, BOPO, GCG , and CAR is a ratio that is included in the good criteria. The results of the independent sample t-test (test two average differences) were obtained that the GCG and Capital factors as measured by the composite value of the bank's self-assessment GCG and the CAR ratio there was no significant difference between BPD Sulselbar and BPD Kaltimtara while the risk factor profile and earnings as measured by the ratio of NPL, LDR, ROA and BOPO there are significant differences between BPD Sulselbar and BPD Kaltimtara during the 2015-2020 period.